Effects of High-Dose Vitamin D Supplementation on Phase Angle and Physical Function in Patients with Prostate Cancer on ADT. (26th November 2021) - Inglis, Julia E.; Fernandez, Isabel D.; van Wijngaarden, Edwin; Culakova, Eva; Reschke, Jennifer E.; Kleckner, Amber S.; Lin, Po-Ju; Mustian, Karen M.; Peppone, Luke J.
Abstract: Purpose: Androgen deprivation therapy (ADT) is commonly used to treat patients with advanced prostate cancer but is associated with functional decline. Bioelectrical impedance analysis (BIA)-derived phase angle may reflect frailty and functional decline in cancer patients. High-dose vitamin D supplementation may improve phase angle values and physical function. Methods: We conducted an exploratory analysis from a phase II randomized controlled trial investigating the efficacy of high-dose vitamin D supplementation in prostate cancer patients (age ≥ 60 yrs). Fifty-nine patients were randomized to high-dose vitamin D (600 IU/day plus 50, 000 IU/week) or low-dose: RDA for vitamin D (600 IU/day plus placebo weekly) for 24 weeks. Phase angle was measured by BIA. Physical function measures included handgrip strength, 6-minute walk test, Short Performance Physical Battery and leg extension. All testing was completed at baseline, week 12 and week 24. Results: Phase angle values were wider over the entire study in the high-dose vitamin D arm indicating healthier muscle cells. The low-dose vitamin D arm had phase angle values consistent with frailty cutoffs in older men (<5.7°). Conclusion: Patients in the high-dose vitamin D arm experienced wider phase angle values over the course of the study which may indicate less frailty. ClinicalTrials.gov ID: NCT02064946.